Risks of Digital Exclusion - Traugott Böttinger; Anja Kürzinger; Lea Schulz (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung, 2023)
Teaching in primary schools means taking the heterogeneity of students’ backgrounds, skills, and capacities into account and offering them a commensurately wide variety of learning opportunities. This is particularly the case when it comes to digital-based instruction, which often entails individualized learning and greater responsibility of learners for their own learning processes. To enable participation and reduce risks of exclusion – for students with disabilities and in the context of the digital divide – teachers’ learning support is of great importance. Despite the potential of teacher support for learning with digital media, few studies have investigated this topic. This paper introduces a research study using videography to analyze the learning support given by preservice teachers during active media work. The findings indicate that teachers tend to provide mainly direct instruction, and significantly less diagnostic support aimed at fostering the learning process. The results do not confirm the idea that digital teaching formats provide technical rather than content support. Furthermore, they show that digital learning formats enable participation by all the students in the class. These results are discussed with a view to risks of exclusion and implications for teacher professionalization.